NILAI NORMAL LATENSI DAN AMPLITUDO GELOMBANG VISUAL EVOKED POTENTIAL PADA USIA DEWASA - Wijaya, Ade; Hakim, Manfaluthy; Ibrahim, Nurhadi; Prihartono, Joedo (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2018)
NORMATIVE VALUES OF VISUAL EVOKED POTENTIALS` LATENCIES AND AMPLITUDES IN ADULTSABSTRACTIntroduction: Visual evoked potentials (VEP) is used to assess the visual pathway through the optic nerves and brain. VEP wave can be affected by physiological and non-physiological factors; some of which can be controlled, while others cannot. Thus, each VEP laboratory needs its own set of normative values. A normal VEP response to a stimulus is a positive occipital peak that occurs at a mean latency of 100ms. Most of the published normal value originated from abroad where demographical and environment condition are considered less appropriate with Indonesian population.Aims: To established normal value of adult VEP latency and amplitude in Clinical Naeurophysiology Laboratori- um, Neurology Clinic Dr. Cipto Mangunkusumo Hospital, Jakarta.Method: A cross-sectional study on healthy subject between 18 to 55 years old. The anthropometric parameters including age, height, weight, body mass index and head circumference were recorded in all the subjects. VEP was record- ed with a Caldwell Sierra Summit machine and standard silver-silver chloride disc electrodes. A VEP monitor displaying checker board was used to give the pattern reversal stimulus. The VEP parameters recorded were latencies to P100 waves.Results: P100 latencies on 110 subjects, 55 male, and 55 female upon recording at 32’ check size were 117ms in male and 119 ms in female. Upper normal limit of interocular latency difference values in recording at the same size were 10,96ms in male and 10,2ms in female. No significant differences of P100 latencies between male and female were found, but there were significant differences in amplitudes.Discussion: In our population, gender is an important factor affecting P100 amplitudes but not P100 latencies.Keywords: Amplitude, latency, P100, visual evoked potentialABSTRAKPendahuluan: Visual evoked potentials (VEP) digunakan untuk menilai jaras visual dari nervus optikus hingga korteks visual. Gelombang VEP dapat dipengaruhi oleh berbagai faktor fisiologis dan non-fisiologis yang tidak semua dapat dikontrol, sehingga diperlukan referensi nilai normal latensi dan amplitudo gelombang VEP untuk di setiap laborato- rium. Sejauh ini mayoritas referensi berasal dari studi di luar negeri yang secara demografi maupun kondisi setempat dapat kurang sesuai dengan populasi di Indonesia.Tujuan: Mengetahui nilai normal latensi dan amplitudo gelombang VEP pada subjek dewasa di Laboratorium Neurofisiologi Klinik, Poliklinik Saraf RSUPN Dr. Cipto Mangunkusumo, Jakarta, sebagai referensi pemeriksaan VEP di kemudian hari.Metode: Studi potong lintang pada subjek sehat berusia antara 18 hingga 55 tahun. Subjek diukur antropometri, seperti usia, tinggi badan, berat badan, indeks massa tubuh, dan lingkar kepala. Perekaman VEP menggunakan alat Cald- well Sierra Summit, dan elektroda elektroensefalografi (EEG) standar. Stimulus VEP menggunakan layar berpola dan metode transient pattern reversal. Parameter VEP yang direkam adalah latensi dan amplitudo P100.Hasil: Pada perekaman terhadap 110 subjek yang terdiri dari 55 subjek laki-laki dan 55 subjek perempuan dengan ukuran kotak 32’, nilai batas atas latensi gelombang P100 adalah 117ms pada laki-laki dan 119ms pada perempuan. Nilai batas atas perbedaan latensi interokular pada perekaman dengan ukuran kotak yang sama adalah 10,96ms untuk laki-laki dan 10,2ms untuk perempuan. Tidak ada perbedaan bermakna antara latensi gelombang P100 pada kelompok laki-laki dan perempuan, tetapi terdapat perbedaan amplitudo P100 yang bermakna antara kelompok laki-laki dan perempuan.Diskusi: Terdapat perbedaan yang bermakna pada rerata amplitudo P100 antara subjek laki-laki dan perempuan pada perekaman dengan ukuran kotak 16’ maupun 32’.Kata kunci: Amplitudo, latensi, P100, visual evoked potentials